THE INFLUENCE OF MACROECONOMICS VARIABLES: RUPIAH / USD, BI RATE: INFLATION, AND THE WORLD OIL PRICES ON THE RETURN OF SHARES OF MANUFACTURING SECTOR 2006-2015 - Sahetapy, Mendy Thensya; Kennedy, Posma Sariguna Johnson (Fundamental Management Journal, 2017)
2008 global economic crisis has led to poor growth across all sectors in Indonesia. The crisis also had an impact on stock market conditions that exist in Indonesia, including the shares of the manufacturing sector. The stock price itself more easily influenced by external factors or changes in macroeconomic conditions. Macroeconomic factors will continue to experience growth and development as always turmoil fluctuation, well after the global crisis well so far. Therefore, this study aims to determine how large the macro-economic factors that influence the stock return of the manufacturing sector. Macroeconomic factors that will be examined is the exchange rate USD / USD, BI rate, inflation and oil prices. The analytical method used in this research is multiple regression analysis were performed with SPSS 23. One of the requirements to perform multiple test analysis necessary to test classic assumptions. This is necessary so that the resulting regression equation is BLUE (Best, Linear, Unbiased, Estimator). In addition to assessing the goodness of fit of a model made for the t-test, F, and test the coefficient of determination. This study uses monthly data from 2006-2015. The results of this study indicate that the variable Exchange Rate / USD, oil prices negatively affect Sunia Stock Return manufacturing sector 2006-2008 period and a variable BI Rate, Oil Price Inflation influence positively and negatively affect the manufacturing sector Stock Return period 2010-2015.Keywords: global crisis in 2008, Manufacturing Sector, Exchange Rate, BI Rate, Inflation, Oil Price, Stock Return.